Teenage Childbearing and the Welfare State - Georgi Kocharkov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Teenage childbearing is a common incident in developed countries. However, the occurrence of teenage births is much more likely in the United States than in any other industrialized country. The majority of these births are delivered by female teenagers coming from low-income families. The hypothesis put forward here is that the welfare state (a set of redistributive institutions) plays a significant role for teenage childbearing behavior. We develop an economic theory of parental investments and risky sexual behavior of teenagers. The model is estimated to fit stylized facts about income inequality, intergenerational mobility, and sexual behavior of teenagers in the United States. The welfare state institutions are introduced via tax and public education expenditure functions derived from U.S. data. In a quantitative experiment, we impose Norwegian taxes and/or education spending in the economic environment. The Norwegian welfare state institutions go a long way in explaining the differences in teenage birth rates between the United States and Norway.
Keywords: E24; H31; I28; 330